Exploring presentations of sustainability by US synthetic biology companies. - James Karabin (Public Library of Science (PLoS), 2021)
The field of synthetic biology is increasingly being positioned as a key driver of a more sustainable, bio-based economy, and has seen rapid industry growth over the past 15 years. In this paper we undertake an exploratory investigation of the relationship between sustainability and synthetic biology, identifying and analyzing sustainability-related language on the public websites of 24, US-based synthetic biology companies. We observe that sustainability is a visible part of the self-presentation of the nascent synthetic biology industry, explicitly mentioned by 18 of the 24 companies. The dominant framing of sustainability on these company websites emphasizes environmental gains and "free-market" approaches to sustainability, with little explicit mention of social dimensions of sustainability such as access, justice or intergenerational equity. Furthermore, the model of sustainability presented focuses on incremental transition towards environmental sustainability through direct substitution of products and processes using bioengineered alternatives (n = 16 companies), with no change in societal consumption or policy frameworks required in order to see sustainability gains. One-third of the companies analyzed (n = 8) mention "nature" on their websites, variously framing it as a resource to be managed or as a source of inspiration; whether the latter signals a potentially more complex relationship with nature than advanced free-market models of sustainability remains to be seen. As the synthetic biology industry begins to grow in size and visibility, we suggest this is an opportune time for the community to engage in explicit deliberation about its approach to sustainability.